Evaluation of Chemical Attributes of Low Chilling Strawberry (Fragraria ananassa) Varieties in Chitwan, Nepal - Shrestha, Bishal; Tripathi, Kalyani Mishra; Shrestha, Arjun Kumar; Gautam, Rajendra (Nepalese Horticulture, 2023)
An experiment to evaluate the qualitative parameters of strawberries to select the promising and high-value varieties was conducted in Bharatpur-5, Chitwan Nepal. The experiment comprises eight varieties ‘Florida Beauty, Florida Festival, Sweet Sensation, Ruby Gem, Elyana, Winter Star, Winter Dawn, and Nyho (check variety) as treatments, laid out in a single factorial RCBD with four replications. The fruits of different varieties were harvested at their respective physiological maturity and fresh juice was extracted for qualitative analysis. The qualitative analyses revealed that the maximum TSS (9.88 °Brix) was recorded in the Nyho variety while the minimum TSS (6.58 °Brix) was recorded in Florida Festival. The maximum amount of TA (0.93 %) and the highest Vitamin C (75.57 mg/100 g) was recorded in fruits of Elyana while the minimum TA (0.71 %) in Sweet Sensation and the lowest amount of Vitamin C (59.89 mg/100 g) was recorded in Nyho. In the case of antioxidant properties of evaluated strawberry varieties, Elyana was found to be superior (81.33 %) while the lowest antioxidant properties were observed in fruits of variety Nyho with a value of 63.23 %. The maximum phenols content (0.64 mg GAE/g) was found on harvested fruits of Nyho while the minimum phenols content (0.24 mg GAE/g) was recorded in fruits of the Winter Star variety. Among the tested varieties, sweetness and aroma were the highest in Nyho while Elyana and Sweet Sensation were superior in nutritional attributes.